Reflective-Metacognitive Learning (RML) in Achieving Higher Order Thingking Skills (HOTS) of KKNI Curriculum - Reksiana Reksiana; Asep Abdul Aziz; Ida Putri Rarasati (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
This research based on the problems of the learning system in Indonesia which a national and international scale. At this time learning must be oriented in Industrial Era 4.0 and the educational paradigm must be change in systems thinking to the top level of Bloom revised taxonomy. The researchers analyzed how to apply using Reflective Metacognitive Learning (RML) model and integrated Garrison, Anderson, and Archer model to achieve Higher Order Thinking Skills (HOTS) of KKNI Curriculum at Institut Ilmu AL Qur’an Jakarta in Islamic study program. This research based on a qualitative approach with descriptive analysis method. The data was obtained from the fifth semester students of Islamic Education Program of Institut Ilmu Al-Quran (IIQ) Jakarta and from all relevant sources such as interviews, observations, and documentations. The findings showed that the application of the Reflective-Metacognitive Learning (RML) model integrated with the Garrison, Anderson, and Archer model was found in the four critical thinking skills of (IIQ) Jakarta students in learning, for instance: (1) students are quick to respond to events (trigger event), (2) students are more able to explore (exploration) (3) students can integrate knowledge into the context of learning (integration) and (4) then students propose (resolution). It was important that the application of these two models can improve the learning process and level of thinking of Higher Order Thinking Skills (HOTS) metacognitive levels. Keywords: High Order Thinking Skills, HOTS, Reflective-Metacognitive Learning, KKNI Curriculum